2022
DOI: 10.1093/noajnl/vdac070
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic susceptibility contrast MRI may contribute in prediction of stereotactic radiosurgery outcome in brain metastases

Abstract: Background Following stereotactic radiosurgery (SRS), predicting treatment response is not possible at an early stage using structural imaging alone. Hence, the current study aims at investigating whether dynamic susceptibility contrast (DSC)-MRI estimated prior to SRS can provide predictive biomarkers in response to SRS treatment and characterize vascular characteristics of pseudo-progression. Methods In this retrospective s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 44 publications
(57 reference statements)
1
1
0
Order By: Relevance
“…Similar results were reported by Kuo et al They found that increased relative CBV can differentiate between tumor recurrence and post-radiation changes in patients with brain metastases [45]. Of interest, Starck et al found that pre-radiotherapy relative CBV and CBV are significantly decreased in patients with brain metastases who had true progression or early death after radiotherapy [46].…”
Section: Quantitative Mri Techniques To Differentiate Between Post-ra...supporting
confidence: 72%
See 1 more Smart Citation
“…Similar results were reported by Kuo et al They found that increased relative CBV can differentiate between tumor recurrence and post-radiation changes in patients with brain metastases [45]. Of interest, Starck et al found that pre-radiotherapy relative CBV and CBV are significantly decreased in patients with brain metastases who had true progression or early death after radiotherapy [46].…”
Section: Quantitative Mri Techniques To Differentiate Between Post-ra...supporting
confidence: 72%
“…Similar results were reported by Kuo et al They found that increased relative CBV can differentiate between tumor recurrence and post-radiation changes in patients with brain metastases [ 45 ]. Of interest, Starck et al found that pre-radiotherapy relative CBV and CBV are significantly decreased in patients with brain metastases who had true progression or early death after radiotherapy [ 46 ]. Using DCE and DSC, Morabito et al found that there is a significant correlation between diagnosing recurrent brain metastases with Ktrans (98% of sensibility and 97% of specificity) and with rCBV (88% of sensitivity and 75% of specificity) [ 47 ].…”
Section: Reviewmentioning
confidence: 99%